Poziom stóp procentowych a wielkość i struktura oszczędności finansowych gospodarstw domowych w Polsce w latach 2000–2013 - Kulpaka, Paweł (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper analyzes the size and structure of the households financial savingsin Poland in the years 2000–2013. Throughout the entire analysis period the valueof savings increased significantly. Bank deposits were the basic category in whichthe personal financial surpluses were invested. The share of alternative investments,primarily securities, rose rapidly in the whole structure of households financial savingsbefore the middle of 2007 at the expense of bank deposits. After the outbreakof the financial crisis in the summer of 2007 the share of bank deposits temporaryincreased while the percentage of the alternative investments diminished. Duringentire period the importance of pension products gradually increased.